PENGARUH KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA PT.MULTILINDO UTAMA BATAM - Dina Agustine; Edwin Agung Wibowo (Universitas Riau Kepulauan, 2016)
The purpose of this research is to know the factors that are influences in determining of costumer satisfaction. Data collected through questionnaires and conducted on 45 respondents. Analysis of the data in this study using SPSS version 20. This chosen by purposive sampling the sample technique based on statistical and research estimated using the formula Rao Purba with an error rate of 10% and testing techniques of data used in this study include testing the validity of the factor analysis, Cronbach alpha reliability test . Classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis. Where, Customer Satisfaction (Y), Service Quality variable (X1), Price variable (X2), and Location variable (X3). Hyphothesis test uses t test demonstrates that the three of examined independent variables is proved significantly have a partially effect on dependent variable of Customer Satisfaction. Then, follow the F test can be recognized that the three of examined independent variables has a simultaneously effect on dependent variable of Customer Satisfaction. The grade of Adjusted R Square is 0,862 demonstrates that 86,2 percent of Customer Satisfaction variable can be explained by the three of independent variables within regression equation. While, the remainder is 13,8 percent is explained by other variables outside of those third variables used in the research.